Switching the Localized Surface Plasmon Resonance of Single Gold Nanorods with a Phase-Change Material and the Implementation of a Cellular Automata Algorithm Using a Plasmon Particle Array. (2nd February 2015) - Hira, Takashi; Uchiyama, Takayuki; Kuwamura, Kenta; Kihara, Yuya; Yawatari, Tasuku; Saiki, Toshiharu
Abstract : We investigate the modulation of the localized surface plasmon resonance (LSPR) of a gold nanorod (AuNR) using a GeSbTe film as an active medium. We demonstrate high-contrast switching of LSPR in an AuNR/GST/Au thin film sandwich structure upon phase change. To go beyond this single-particle switching functionality, we consider a plasmon particle system interacting with a phase-change material (PCM) to discuss the possibility of parallel processing devices with memory functionality, exploiting the plasticity and threshold behavior that are inherent characteristics of PCMs. We demonstrate that the temporal and spatial evolution of a plasmon-PCM array system can be equivalent to a cellular automata algorithm.